Enhanced biogas production from rice straw with various pretreatment : a review - Fahriya Puspita Sari; Budiyono Budiyono (Diponegoro University, 2014)
Rice straw is one of organic material that can be used for sustainable production of bioenergy and biofuels such as biogas (about 50-75% CH4 and 25-50% CO2). Out of all bioconversion technologies for biogas production, anaerobic digestion (AD) is a most cost-effective bioconversion technology that has been implemented worldwide for commercial production of electricity, heat, and compressed natural gas (CNG) from organic materials. However, the utilization of rice straw for biogas production via anaerobic digestion has not been widely adopted because the complicated structure of the plant cell wall makes it resistant to microbial attack. Pretreatment of recalcitrant rice straw is essential to achieve high biogas yield in the AD process. A number of different pretreatment techniques involving using physical pretreatment (hydrothermal and freeze), chemical pretreatment (sodium carbonate – sodium sulfite, hydrogen peroxide, NMMO, alkaline, and dilute acid) and biological pretreatment (fungal pretreatment) also combined pretretment (microwave irradiation and chemical) approaches have been investigated, but there is no report that systematically compares the performance of these pretreatment methods for application on rice straw for biogas production. This paper reviews the methods that have been studied for pretreatment of rice straw for delignification, reducing sugar, and conversion to biogas. It describes the AD process, structural and compositional properties of rice straw, and various pretreatment techniques, including the pretreatment process, parameters, performance, and advantages vs. drawbacks.